Cryptosporidiosis And Other Intestinal Parasitic Infections And Concomitant Threats Among HIV-Infected Children In Southern Ethiopia Receiving First-Line Antiretroviral Therapy - Gebre B (Dove Medical Press, 2019)
Blatu Gebre,1 Tsegaye Alemayehu,2 Mekonin Girma,2 Freshwork Ayalew,2 Birkneh Tilahun Tadesse,3 Techalew Shemelis2 1Hawassa University, College of Natural and Computational Sciences, Department of Biology, Hawassa, Ethiopia; 2Hawassa University, College of Medicine and Health Sciences, School of Medical Laboratory Science, Hawassa, Ethiopia; 3Hawassa University, College of Medicine and Health Sciences, Department of Pediatrics and Child Health, Hawassa, EthiopiaCorrespondence: Tsegaye AlemayehuHawassa University College of Medicine and Health Sciences, School of Medical Laboratory Science, P.O. Box: 1560, Hawassa, EthiopiaTel +2519-13-872-24-12Email alemayehutsegaye@ymail.comBackground: Children infected with human immunodeficiency virus (HIV) are at high risk of acquiring intestinal parasitic infections. This study aimed to determine the magnitude of Cryptosporidium and other intestinal parasitic infections and concomitant threats among HIV-infected children.Methods: A hospital-based cross-sectional study was carried out at three antiretroviral therapy clinics in southern Ethiopia from February 2016 to June 2017 in 384 HIV positive children. Socio-demographic and clinical data were collected using structured questionnaires. Direct stool microscopic examination and modified Zeihl–Neelsen staining technique to identify parasites. Chi-square test was conducted to determine the real predictors of the infection. Significant association was considered when p-value <0.05 at 95% CI.Results: The overall magnitude of intestinal parasitic infections among the study population was 16.9% (95% CI: 13.0–20.8%). The most predominant parasitic infections were Cryptosporidium spp. (9.6%) and the least was Taenia spp. (0.78%). Diarrheal status (χ2=7.653, df=2, p=0.022) was detected to be the only significant associated variable.Conclusion: Cryptosporidium infection was found to be the most common intestinal parasitosis among HIV-infected children. Routine screening service for Cryptosporidium and other intestinal parasites is important in the clinical management of HIV-infected children.Keywords: intestinal parasites, Cryptosporidium, HIV/AIDS, Southern Ethiopia